2018
DOI: 10.1111/tbed.13068
|View full text |Cite
|
Sign up to set email alerts
|

Global knowledge gaps in the prevention and control of bovine viral diarrhoea ( BVD ) virus

Abstract: The significant economic impacts of bovine viral diarrhoea (BVD) virus have prompted many countries worldwide to embark on regional or national BVD eradication programmes. Unlike other infectious diseases, BVD control is highly feasible in cattle production systems because the pathogenesis is well understood and there are effective tools to break the disease transmission cycle at the farm and industry levels. Coordinated control approaches typically involve directly testing populations for virus or serological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 89 publications
(133 reference statements)
1
57
0
2
Order By: Relevance
“…In contrast to vaccination, biosecurity reduces BVDV production losses more effectively (Table ). This may be related to the fact that farmers often fail to apply the vaccine correctly, vaccines are not proven to be fully protective (Evans et al, ), e.g., in the prevention of in‐utero transmission of the virus (Moennig & Brownlie, ), the BVDV vaccine does not provide life‐long immunity and hence periodic vaccination is required (Weldegebriel, Gunn, & Stott, ), live BVDV vaccine could be contaminated with other viruses (Lindberg, ), and/or a critical vaccination coverage rate should be reached to prevent new PI animals (Scharnböck et al, ). In the present multivariate‐regression, testing and culling was not identified as a significant factor in changing the mean annual production losses per animal due to BVDV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to vaccination, biosecurity reduces BVDV production losses more effectively (Table ). This may be related to the fact that farmers often fail to apply the vaccine correctly, vaccines are not proven to be fully protective (Evans et al, ), e.g., in the prevention of in‐utero transmission of the virus (Moennig & Brownlie, ), the BVDV vaccine does not provide life‐long immunity and hence periodic vaccination is required (Weldegebriel, Gunn, & Stott, ), live BVDV vaccine could be contaminated with other viruses (Lindberg, ), and/or a critical vaccination coverage rate should be reached to prevent new PI animals (Scharnböck et al, ). In the present multivariate‐regression, testing and culling was not identified as a significant factor in changing the mean annual production losses per animal due to BVDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Large epidemiological studies and detailed documentation of production data are rare. Richter et al, () demonstrated that production losses vary considerably in the literature due to uncertainty and knowledge gaps regarding the epidemiology of BVDV infections (Evans et al, ). Although different epidemiology and mitigation situations were taken into account, the estimated mean annual production losses per animal in this work can only give rough indications of the true annual economic impact of BVDV on production due to the uncertainty of how representative individual studies actually are for the whole cattle population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Therefore, farmers need to be motivated both to change existing behaviours and to implement effective biosecurity practices to reduce the risk of disease introduction. [33][34][35] MCA and TSCA show that there are three main farm typologies in relation to the implementation of biosecurity measures differentiated mainly by region (which implies different implementation of BVDV and BoHV-1 control programmes) and herd size. Although some biosecurity limitations were common, others were more specific to each cluster, similar to the observation made by Sarrazin and others.…”
Section: Discussionmentioning
confidence: 99%
“…Biosecurity is defined as actions that are implemented to prevent pathogens from entering a herd and minimise the spread of pathogens within a herd [18][19][20]. Increased herd immunity can be achieved by vaccination or exposure of naïve cattle to PI cattle (often termed "deliberate exposure" when used as a control method) [21][22][23]. Pestigard ® , an inactivated vaccine, is the only commercially available vaccine within Australia [24].…”
Section: Introductionmentioning
confidence: 99%